The Ethics of Contingency: An Alternative (to) Morality in the Analects - D’Ambrosio, Paul (Religions, 2023)
An appreciation of the emphasis on flexibility in the Analects is one of the most consistent motifs in the various interpretations of this text. When applied specifically to normative readings, embracing adaptability, having malleable standards, and taking particulars into account are both promising and challenging ways to think about whether something might be moral or ethical. This paper attempts to deconstruct this familiar discussion along novel lines that can reveal new ways to reflect on the importance of flexibility in the Analects, while, at the same time, it reconstrues ways in which comparative projects might be oriented. The main argument is this: the Analects does not recognize a categorical distinction between a moral and non-moral realm. Whereas, in much modern academic thought, there is a distinction between what counts as contingencies and what is up to the individual, which, in turn, loosely corresponds to the non-moral and moral realms, the Analects does not make such clear distinctions. Everything, including core moral issues such as the individual’s own choice, moral guidelines, and the contextualization of (moral) models, is all ultimately grounded in contingencies. Nevertheless, the Analects provides ways of reflecting on choices and actions that aim to steer people in specific directions. We may understand this as a type of morality, but one that is significantly distinct from those wherein the difference between the moral (non-contingent) and non-moral (contingent) is foundational.